Hot wall growth and properties of lead telluride films doped by germanium and gallium - Lashkarev, G.V.; Radchenko, M.V.; Slynko, E.I.; Vodopiyanov, V.N.; Asotsky, V.V.; Kaminsky, V.M.; Beketov, G.V.; Rengevich, E.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
The researches results of films (PbTe)₁₋y(GaTe)y and (Pb₁₋xGexTe)₁₋y(GaTe)y of n-type conductivity with carrier concentration within (2⋅10¹⁷÷9⋅10¹⁸) cm⁻³ are represented. The films were growth by modified hot wall technology on barium fluoride substrate. A state of films surface was investigated by Atomic Force Microscope using both contact and taping modes. Hall coefficient, specific resistivity and thermoelectromotive force of films were measured in the temperature range 77-300 K. The investigation showed that the presence of germanium leads to an appearance of significant features on temperature dependencies of termoelectro-motive force which are connected with phase transition of displacement type. Doping gallium leads to n-type conductivity of films which increases with impurity concentration. The ionization energies of Ga impurities levels (n - exp(-E/2kT)) were within 3÷10 meV. The change of energy position and width of impurity level with increase of impurity concentration is established. The unusual protrusions on terraces of growth were discovered. The tops of protrusions can be considered as quantum dots. Inasmuch as composition of protrusions is expected to be distinguished from that of the terraces, they can create pieces of quantum wires.